KOORDINASI APARAT KEPOLISIAN DAN LEMBAGA TERKAIT DALAM RANGKA PENANGGULANGAN KEJAHATAN JALANAN DAN PREMANISME - Fitria Meizaroh (Universitas 17 Agustus 1945 Samarinda, 2013)
ABSTRAKSIThe impact of the growing number of unemployed and supported by the higher poverty rates resulted in one heart to do evil and the economic pressure many people who take shortcuts by any means to earn money, so that this problem causes to grow and increased racketeering practices that causing a lot of problems and concerns for the community. Police in this regard relates to its function as a protector of the public has a very big role in the response to the thuggery. Police were so close to the people expected to take appropriate action in addressing the phenomenon of gangsterism in the community.